Fit for a king [videorecording] - Barrat, James; Barrt, James; Grant, Eleanor; Iwata, Mary Ellen; Janse, Andre; Kaptijn, Ellen; McDonald, Jack; Okkerse, Ton; Schots, Frank; Schroevers, Martijn; Van Oosten, Ageeth Hogervorst, Thij's (Great Palaces of the World)
At Hampton's Court Palace built by a Cardinal and stolen by King Henry VIII beheaded two of his wives, and changed the course of history. At the Palace of Schonbrunn in Vienna, Marie Antoinette grow up, Mozart debuted and the oldest empire in Europe died. From the Escorial, Phillip II of Spain laid the groundwork for his great Armada and the ruin of Spain. and on the coast of California, newspaper mogul William Randolf Hearst built a fantasy palace to entertain the royalty of Hollywood.